The Best of Business Economics Highlights from the First Fifty Years. - National Association for Business Economics; Crow, Robert Thomas; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
In celebration of the Business Economics journal's 50th anniversary, this collection brings together the best articles from half a century of publication.
Keywords: Science; Science; Science, general; Electronic books